Idelogy, modernization and politics in India - Mehta, V.R. (Delhi, 1988)
After about thirty-five years of independence, there is a growing realization in the country that the present democratic forms and structures based on the Westminster model are not working satisfactorily. This book seeks to examine the relevance of both liberal-democratic and Marxist ideologies in terms of the working out of such ideas into practice as 'centre and periphery', 'base and superstructure' and the individual and the community. It looks at the Indian Polity as a development of an organic being, unravels the cleavages within it between political, economic and social practices, and emphasises the need to develop a cohesive political centre which will not only be strong enough to resolve these conflicts and cleavages but also go beyond it and become a powerful catalyst for the consolidation and development of national identity based on political order, economic development, social justice and above all, a new consensus of values which the late nineteenth century renaissance brought to surface but could not concretize in terms of new structures. The book also seeks to suggest these alternative structures so that the unity. in diversity in the structural arrangements of society not only becomes more real but also lines of communication between polity, economy and society more clear and enduring.
Keywords: Political Science